Assessment of epidemiological determinants of obesity among nursing staff in a tertiary healthcare center in northern Maharashtra: a cross sectional study - Borde, Anant N.; Kinge, Amol D.; Bawa, Mukesh; Pagar, Vikrant; Vyas, Parth (International Journal Of Community Medicine And Public Health, 2017)
Background: Obesity is now-a-days is considered as diseases. India is currently experiencing rapid epidemiological transition. Doctors and nurses play a vital role in the health and welfare of the people of a nation. Health of the doctors and nurses is of paramount importance and they are also known to have a sedentary lifestyle with high levels of stress and their own health behaviours are known to influence the public's confidence in advice offered. The purpose of this study is to find out prevalence of obesity among nurses and to assess its epidemiological determinants. Methods: It was a cross sectional study done among 200 nursing staff working in a tertiary healthcare center in Northern Maharashtra between September 2016 to March 2017. Data regarding socio-demographic profile, complete lifestyle history and general and systemic examinations were gathered and analysed using appropriate methods. Results: Out of total 200 nurses enrolled for the study 24% were males and 76% were females. All the participants were between the age group of 20-60 years. About 13% had altered sleep pattern while 15.5% women had menstrual irregularities. Overall prevalence’s of underweight, overweight, obesity and morbidly obese were found to be 8%, 27%, 13% and 3.5% respectively. Conclusions: Based on findings of the present study, we conclude that total prevalence of malnutrition (under nutrition plus over nutrition) found in this study was 51.5% and it was found to be associated with various modifiable risk factors.